2009
DOI: 10.1007/s00701-008-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Adverse radiation effects after Gamma Knife Surgery in relation to dose and volume

Abstract: The relationship between target volume and the risk of adverse radiation effects may not apply with lower prescription doses. Individual radiosensitivity may explain why a minority suffer AREs unrelated to target volume. It is possible that radiation-induced brainstem parenchymal damage with concomitant cranial nerve deficits may be commoner after radiosurgery than is usually thought. If tumour control with lower doses is adequate, radiosurgery could be safely considered for larger targets associated with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 85 publications
2
28
1
Order By: Relevance
“…Thus, the frequency with which said findings are reported varies from one study to the next. Foroughi et al 12 reported a 2.2%-9% incidence of necrotic masses after SRS, while Ganz et al 13 reported a 60% incidence for radiation-induced changes. Several factors, including radiation dose and target vol- ume, are reported as important predictors for radiological changes.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the frequency with which said findings are reported varies from one study to the next. Foroughi et al 12 reported a 2.2%-9% incidence of necrotic masses after SRS, while Ganz et al 13 reported a 60% incidence for radiation-induced changes. Several factors, including radiation dose and target vol- ume, are reported as important predictors for radiological changes.…”
Section: 21mentioning
confidence: 99%
“…Several factors, including radiation dose and target vol- ume, are reported as important predictors for radiological changes. [12][13][14] Other risk factors for ARE, such as prior hemorrhage, 14 AVM location, 9 and repeated radiosurgery, 4 have been described in some series. In this study, we have assessed overall pretreatment multivariate predictors of favorable outcome in a large patient cohort undergoing GKRS.…”
Section: 21mentioning
confidence: 99%
“…Furthermore, it is worth stressing that -even treating larger volumes -either with reduced dosages or with fractionated schedules, the literature shows no evidence of significantly increased "Adverse Radiation Effects" ("ARE"). Probably because the risk of "ARE" gradually subsides with lower prescription doses (3,18,19,22,31,38,47,49,64,65,70).…”
Section: Gamma Knife Radiosurgerymentioning
confidence: 99%
“…dose volume integral, conformity index etc. (6,20,22,56,72,83,86) However, recent reports have emphasized the extremely high chances to maintain adequate LTC rates -without increasing side effects-by treating larger meningiomas with either fractionated schedules or reduced dosages (3,13,18,19,22,24,31,32). b. the controversial or disappointing results obtained in atypic and anaplastic lesions (17,25,27,30,51,73), sometimes characterized by intra-or extraneuraxis metastatization (17) or by enhanced growth after radiosurgery (6,14,42); c. the still pronounced morbidity rate of this technique on sensory nerves (6,14,77).…”
Section: Anaplastic (Gr 3) Meningiomamentioning
confidence: 99%
“…In particular, the volume around the AVM's target exposed to 12 Gy or more carries an increased risk of radiological and clinical radiation damage [43,[70][71][72] . Our limited number of complications is probably related to small volumes treated and to the relatively low doses used.…”
Section: Radiation-induced Complicationsmentioning
confidence: 99%